Study on Ageing Process of Polymer Modified Bitumen - Nurul 'Izzati, Ab Rahim (2012)
Bitumen is a very complex combination of organic compound and contain high proportion of hydrocarbons with high carbon numbers. The main application of bitumen is in road industry because of its good adhesion to mineral aggregates and its physical properties. The major failure modes using only bitumen in the road construction are rutting, cracking and ageing. In cold climates, cracking in pavements may be an extensive problem. Low temperature cracking is caused by thermally induced tensile stresses exceeding the tensile strength of the pavement material. By modified the bitumen using polymer which is Ethylene Vinyl Acetate (EVA) is an alternative to increase the physical and chemical properties of 80/100 bitumen due to short term ageing effect. The sample of polymer modified bitumen is prepared using Toluene as a solvent to bind the polymer with bitumen. The sample then undergoes the short term ageing process using Thin Film Oven (TFO) before being characterized using FTIR, microstructure analysis, penetrometer, viscometer and TGA. The increasing of EVA content in bitumen will increase the viscosity of sample and will reduced the value of penetration.